Grammatical Problems Experienced by English Department Students at Vocational Higher Education - Siti Aisyiyah (Universitas Muhammadiyah Prof. DR. HAMKA, 2019)
Learning English as a second language requires students to learn English skills and components, including grammar. English Department students, as second language learners, are required to have good grammar acquisition. However, they usually make errors related to grammatical rules. This study was aimed to identify and analyze some grammatical problems experienced by the English Department Students, Politeknik Negeri Jember. The research result is hoped to be beneficial not only for language learning and teaching, but also for linguistics studies. The data were taken from the students who enrolled Upper Intermediate Grammar Course. The students’ written works were analyzed to find the problems. The first step was reading the works carefully to find grammatical problems. Having identified the problems, the researcher wrote notes about error kinds. She classified the errors into different categories based on their kinds. Then, the researcher analyzed the data and counted using percentage calculation. This study found that the students made the grammatical problems mostly on sentence constructions, numbers, and tenses. Hopefully, the findings would be beneficial for English teachers to get information about grammatical mistakes frequently made by the students, analyze causes of grammatical errors, and find solution to deal with the problems. Keywords: grammatical errors, sentence construction, numbers, tenses